PROSES SELEKSI PENERIMAAN PESERTA DIDIK BARU (PPDB) SECARA ONLINE DI SMK NEGERI 1 GUNUNG TALANG KABUPATEN SOLOK - Naufal Raid; Dian Rizke; Jibril Bin Khadafi (Jurnal Public Administration, Business and Rural Development Planning, 2020)
The research objectives are: 1) To find out how the acceptance of new students (PPDB) at SMK Negeri 1 Gunung Talang, Solok Regency. 2) To find out what factors affect the academic achievement of students at SMK Negeri 1 Gunung Talang, Solok Regency. 3) To find out what is the impact of the results of the selection of New Student Admissions (PPDB) on the academic achievement of students at SMK Negeri 1 Gunung Talang, Solok Regency. This study uses a qualitative method, where the researcher tries to describe all phenomena, symptoms, events in accordance with the research problem as it is. The nature of the qualitative approach is intended to present information or information arranged in such a way that it is able to provide a clear and real picture of the object of research. Some data uses are only used as a support for the descriptions used, so as to provide a clear and concrete picture. Based on the descriptions in the previous chapters, the authors draw the following conclusions: 1) Online Selection for New Student Admissions (PPDB) at SMK Negeri 1 Gunung Talang Solok Regency includes: a) Provisions for the Selection of New Student Admissions (PPDB), b) New Student Admissions Mechanism (PPDB), c) The number of applicants accepted at SMK Negeri 1 Gunung Talang. 2) The obstacles faced include: a) There are still people who do not understand (lay) in terms of procedural or technical problems regarding PPDB Online, b) Availability of Internet Connection during the implementation of PPDB Online, c) The number of PPDB Online operators is not proportional to the number PPDB online participants. 3) Efforts made in overcoming the obstacles faced include: a) Carrying out extensive socialization for the community so that they can clearly understand the PPDB online procedure, b) increasing the number of PPDB Online operators